Forward trunk lean with arm support affects the activity of accessory respiratory muscles and thoracoabdominal movement in healthy individuals - Mesquita Montes, António (2022)
Despite the reported benefits of postures involving leaning the trunk forward with arm support for relieving dyspnea, how those postures influence the mechanics of breathing remains unclear. In response, the aim of the study reported here was to evaluate how posture (i.e., standing and sitting) and leaning the trunk forward with arm support affect the activity of accessory respiratory muscles and thoracoabdominal movement in healthy individuals. Thirty-five volunteers (15 males and 20 females) aged 18-29 years breathed with the same rhythm in standing and sitting positions while upright and while leaning the trunk forward with arm support. Surface electromyography was performed to assess the activity of accessory inspiratory (i.e., during inspiration) and abdominal (i.e., during inspiration and expiration) muscles, and a motion capture system was used to assess thoracoabdominal movement. Results revealed that upper trapezius activity was significantly lower in forward-leaning postures than in upright ones (P = 005; ηp2 = 0.311), although the activity of the sternocleidomastoideus and scalenus (P < 0.001; ηp2 = 0.427-0.529), along with the anterior-to-posterior movement of the upper ribcage (P < 0.001; ηp2 = 0.546), were significantly greater in forward-leaning postures than in upright ones. The activity of the external oblique and transversus abdominis/internal oblique was significantly lower in sitting than in standing postures (P < 0.050; ηp2 = 0.206-0.641), and though the activity of the transversus abdominis/internal oblique was significantly lower in forward-leaning than in upright postures (P ≤ 0.001; ηp2 = 0.330-0.541), a significantly greater anterior-to-posterior movement of the abdomen was observed (P < 0.001; ηp2 = 0.662). However, the magnitude of the lower ribcage's medial-to-lateral movement was significantly lower in forward-leaning than in upright postures (P = 0.039; ηp2 = 0.149). Leaning the trunk forward with arm support not only increased the use of accessory inspiratory muscles but also decreased the use of the transversus abdominis/internal oblique, which improved thoracoabdominal movement.